Therapeutic Intervention for the Physically Handicapped - Spillios, James; Janzen, Henry L. (Canadian Journal of Counselling and Psychotherapy, 2012)
The need for training counsellors specifically for intervention with the physically handicapped is the major focus of this article. Definitions of disabilities, rehabilitation and emotional factors are stressed as important variables in physicaland psychotherapeutic treatment. The authors review some of the psychological aspects in counselling the physically handicapped. Comparative studies are reviewedwhich indicate that although there are many commonalities in counselling physically able and disabled clients, special attention is given to those factors in the counselling process that are unique to a physically handicapped client-counsellor relationship.